Hydraulic Analysis and Performance Evaluation of Combined Trunk Sewers: a Case Study of Baghdad City. (Journal of Engineering, 2019)
Sewer system plays an essential task in urban cities by protecting public health and the environment. The operation, maintenance, and rehabilitation of this network have to be sustainable and scientifically. For this purpose, it is crucial to support operators, decision makers and municipalities with performance evaluation procedure that is based on operational factors. In this paper, serviceability and performance indicator (PI) principles are employed to propose methodology comprising two enhanced PI curves that can be used to evaluate the individual sewers depending on operational factors such as flowing velocity and wastewater level in the sewers. To test this methodology; a case study of al-Rusafa in Baghdad city is studied in which two combined trunk sewers are serving (Zeblin and ET-trunks). Hydraulic analysis for two scenarios (average and peak dry weather flows) is performed; afterward, performance evaluation showed a sub-index ranging from 0.5 (minimum level of performance) to one (excellent performance) which implicate that these two trunks, if well maintained will provide sufficient service to the catchment. By applying the serviceability and PI principles; a prioritizing tool is provided which help decision makers towards better management of the sewerage system.